The effect of standardized honey on mucosal healing of the nose and paranasal sinuses after polypectomy: A randomized controlled, double blind pilot study: Honey and mucosal healing after polypectomy - Movahed, Rahman; Rajabi, Omid; Azizi, Hoda; Jafari, Sogol; Yousefi, Razieh; Bakhshaee, Mehdi (Acta Biomedica Atenei Parmensis, 2022)
Objectives: Nasal polyposis (NP) is a chronic inflammatory disease. Honey has several anti-microbial, anti-oxidants, healing, and anti-inflammatory properties which may reduce the need for steroids in this situation. Therefore, the aim of this study is to show the effect of standardized honey on mucosal healing of the nose and paranasal sinuses after polypectomy. Design and method: In this double-blind, randomized, placebo-controlled clinical trial, 28 patients with nasal polyposis underwent functional endoscopic sinus surgery (FESS). Besides common post-op medications, normal saline (as a placebo) and diluted processed honey were used separately in the two nostrils of each patient. Two endoscopic follow-ups using the Philppot-Javer (P-J) scoring system were performed to assess the healing and recurrence of polyps on either side. The secondary outcome measure was the patients' satisfaction rate. Results: The patients’ mean age was 38.03±11.9 years. 15(57.7%) had a positive prick test and also 15(57.7%) had dense eosinophilic infiltration in their surgical specimens. In the first and second follow-up sessions, total P-J scores showed better results for honey in comparison to the normal saline side but that results were not significantly different (P=0.93, P=0.07); whereas it is fair to say that in the second follow-up, the ethmoid and maxillary sinuses demonstrated a greater difference compared to the other sites based on their averages but there were not significantly meaningful (P=0.05, P=0.06). The total score also showed better results for honey in comparison to the normal saline side but was statistically insignificant (P=0.07). Conclusion: Diluted honey seems to have certain positive effects in reducing post-operative edema and the recurrence of nasal polyps in at least the ethmoid and maxillary sinuses; although this positive effect did not result in significant changes. (www.actabiomedica.it)